Instituições e comércio: a proximidade institucional afeta o comércio internacional? - Mariano, Lucas de Castro (2019)
The recent empirical literature has approached the mechanisms that institutions can affect trade flows, however there are few studies that intend to capture the institutional proximity between the countries and which are the effects on trade levels. For that reason, this paper aims to fill this gap. Therefore, six different categories of institutions are considered from the World Bank’s Governance Indicator (WGI) databank and an empirical approach that allows to overcome the following issue imposed by the previous literature: identify the impact of institutions with the inclusion of fixed effects would arise an identification problem that limits the results analysis when is intended to measure the effect from national institutions over trade flows, since they are perfectly collinear with the fixed effects. The countries are classified according to their income (North or South) for four different years, which allows to estimate the impact of institutional changes through the time. Beyond, it is estimated the quality of the goods commercialized in each group. In general, the results shows a negative impact on trade and quality of the goods as the more distant are the institutions between the origin country and the country of destiny.